PENERAPAN PRINSIP FIRST COME FIRST SERVED DALAM PENYELESAIAN TUMPANG TINDIH WILAYAH IZIN USAHA PERTAMBANGAN - Ahmad Redi; Susanto Dharma (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
Indonesian mining industry have undergone impressive pace of development that dispute concerning overlapping on Mining Business License Area which triggers Mining Business License cancellation or revocation. One of such incidents occur between PT Kemakmuran Pertiwi Tambang and PT Wana Kencana Mineral, whereas both companies obtained Mining Business License for the same commodity on the same Mining Business License Area. How can legal certainty be relied upon concerning the Operation Production Mining Business License for holders of Exploration Mining Business License on the overlapped Mining Business License Area based on Mining Law and does the revocation conducted by the Governor of North Maluku has been in accordance with the applicable regulation? To answer both issues above, the author utilized normative qualitative analysis technique and interviews as supporting data. Based on Law No. 4 Th. 2009 concerning mineral and coal mining Article 46, every holder of Exploration Mining Business License shall reserve the right to obtain Operation Production Mining Business License and by using "first come first served" system, PT Kemakmuran Pertiwi Tambang should have the first right to obtain Mining Business License since they have obtained the Exploration Mining Business License in 2005. Meanwhile the revocation conducted by the Governor of North Maluku is clearly against the applicable regulations such as Law No. 30 Th. 2014 concerning Government Administration, Law No. 9 Th. 2015 concerning Regional Regulation, General Principles of Good Governance and Article 119 of Mining Law concerning the terms for Mining Business License revocation.